Antibody Therapy for Pediatric Leukemia - Vedi, Aditi; Ziegler, David S. (Frontiers in Oncology, 2014)
Despite increasing cure rates for pediatric leukemia, relapsed disease still carries a poor prognosis with significant morbidity and mortality. Novel targeted therapies are currently being investigated in an attempt to reduce adverse events and improve survival outcomes. Antibody therapies represent a form of targeted therapy that offers a new treatment paradigm. Monoclonal antibodies are active in pediatric acute lymphoblastic leukemia (ALL) and are currently in Phase III trials. Antibody-drug conjugates (ADCs) are the next generation of antibodies where a highly potent cytotoxic agent is bound to an antibody by a linker, resulting in selective targeting of leukemia cells. ADCs are currently being tested in clinical trials for pediatric acute myeloid leukemia (AML) and ALL. Bispecific T cell engager (BiTE) antibodies are a construct whereby each antibody contains two binding sites, with one designed to engage the patient’s own immune system and the other to target malignant cells. BiTE antibodies show great promise as a novel and effective therapy for childhood leukemia. This review will outline recent developments in targeted agents for pediatric leukemia including monoclonal antibodies, ADCs and BiTE antibodies.